Learning outcomes and achievement among working adult students in the distance and collaborative learning program in Universiti Malaya - Chew, F.P. (2008)
This research is attempt to examine the learning outcomes of the registered adult learners in the distance and e learning program in the Education Faculty, Social Science and Art Faculty and Language Faculty in University of Malaya, Malaysia, particularly at degree and post degree level who have followed the learning modules in distance and e learning. The objective would be to develop an innovative and creative Learning Management System or e class couple with face to face lectures to create highly effective and quality life long education environment. The e learning and teaching culture of the local public universities have great influence in determining the level of achievement and learning outcomes. Demographic factors, such as age, gender, race, marital status, and family background, academic achievement and salary range are other contributing factors that have to be taken into consideration.